Development of Illustrated E-LKPD Media to increase Students' Mathematical Logical Intelligence (Group B Study at PAUD Pembina Negeri 1 Bengkulu City) - Restri Hendayanita (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
This research aims to develop the media of Electronic Student Worksheets (e-LKPD) with Pictures to improve the Mathematical Logical intelligence of group B students, in PAUD Negeri Pembina 1 Bengkulu City. The lack of appropriate use of teaching media and not in accordance with the needs of students causes a lack of students' ability to analyze problem-solving. The research is a development research that adapts the ADDIE development model. There are 5 main stages in this study consisting of stages, analysis, design, development, implementation, and evaluation. The research instruments used are observations, interviews, validation sheets, and tests. The developed products were validated by a team of media experts and the material was then tested in a small group, namely ten students of group B of PAUD Pembina Negeri 1 Bengkulu City. The result of this research is a learning media product made using the Canva application which is applied using a book creator. The results of the response of group B students in a small group trial conducted on 10 students of PAUD Pembina Negeri 1 Bengkulu City, which was 80.49% (good) and the results of the educator's response, which was 96% (very good). Based on the development process starting from the validation of media and materials to the results of small group trials, it was concluded that the learning media product is very feasible and effective to use to increase intelligence.